MANAGING PNEUMOPERICARDIUM IN ADVANCED LUNG CANCER: A CASE REPORT AND LITERATURE REVIEW - Chaaban, Batoul; Arabi, Souraya; Bitar, Hassan; Abou Hamdan, Douaa (Sanamed, 2024)
Introduction: Pneumopericardium, though rare, can lead to severe complications such as cardiac tamponade, particularly in patients with malignancies. This case-based review examines the incidence, management, and outcomes of pneumopericardium in a patient with advanced lung cancer. Case Report: We present a comprehensive literature review and a detailed analysis of a 57-year-old male with metastatic squamous cell carcinoma of the lung, who developed pneumopericardium. The patient’s clinical presentation, diagnostic challenges, and management strategies were documented and compared with similar cases. He presented with cough and dyspnea, and imaging revealed pneumopericardium, likely due to tumor invasion into the pericardial space. Management involved conservative measures, including antibiotics and close monitoring. A literature review revealed that management strategies for pneumopericardium vary based on hemodynamic stability, ranging from conservative treatments to invasive procedures. Recurrence is common, and survival times post-diagnosis are highly variable. Conclusion: Pneumopericardium in cancer patients requires a tailored management approach, with a multidisciplinary team essential for optimizing patient outcomes. This case underscores the need for heightened awareness and prompt, individualized treatment plans for managing such complex conditions.